Pengembangan Instrumen Penilaian Kinerja Praktikum Biologi Materi Sel Sebagai Unit Terkecil Kehidupan: (Development of Performance Assessment Instruments for Biology Practicum Material Cells as the Smallest Unit of Life) - Miftahul Jannah; Afreni Hamidah; Upik Yelianti (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2021)
Performance appraisal is an appraisal based on observations of assessments of student activities as they occur. Assessment is done with the performance, behavior or interaction of students. The development of performance assessment instruments (Performent Assessment) is expected to actively involve students in the learning process. The students will certainly feel motivated in showing their performance, because so far their performance has rarely been assessed, so that their minds are no longer just what needs to be learned, but have improved on what needs to be done. Type This study uses research and development (Research and Development), because it matches the objectives to be achieved. While the research development model chosen is the ADDIE model. Expert validation is carried out by the learning design validator, and the material validator. Practitioner validation is carried out by high school biology teachers. The research subjects were students of SMA N 5 Muaro Jambi class XI IPA, with a total of 6 people for small group trials and 20 people for large group trials. The results of the analysis were obtained that the instruments developed were very helpful for teachers in making assessments when practicum and instruments were suitable for use. Abstrak. Penelitian ini dilatar belakang pentingnya penilaian saat praktikum, biasanya penilaian dilakukan hanya pada laporan paktikum saja, bukan pada setiap proses yang terjadi saat praktikum. Tujuan penelitian mengetahui tahapan pengembangan instrumen penilaian kinerja praktikum pada materi sel sebagai unit terkecil kehidupan. Jenis penelitian ini menggunakan penelitian pengembangan (Research and Development), Sedangkan ModelÂ pengembangan yang digunakan mengadopsi model ADDIE dengan lima tahapan, yaitu: Analisisa (Analysis), Perancangan (Design), Pengembangan (Development), Implementasi (Implementasi), dan Evaluasi (Evaluate). Data kualitatif diperoleh dari saran-saran validator ahli desain instrumen dan ahli materi. Hasil pengembangan validasi ahli desain instrumen diperoleh dengan skor akhir 73,3% dengan kategori layak. Sedangkan validasi ahli materi diperoleh skor 74,7% dengan kategori layak,Â dan respon guru sebagai pengguna instrumen diperoleh skor 80% dengan kategori baik, sehingga dapat disimpulkan instrumen penilaian kinerja praktikum pada materi sel sebagai unit terkecil kehidupan layak untuk digunakan.